Aerodynamic Databank Modeling for Development of a Short-Haul Electric Airliner - Johansson, Anna (My University, 2022)
To the support development of a new airplane, an aerodynamic databank model was developed. The airplane’s performance, stability, control, and handling qualities are analyzed by using a six degrees of freedom airplane model. One of the subsystems to this flight simulation model is the aerodynamic databank model which provides the aerodynamic forces and moments acting on the airplane. Essentially, the aero dynamic databank model is composed of different contributions to the six total aerodynamic coefficients which determine the loads on the airplane. This compo nent buildup method gives a modular architecture of the databank model and makes it easy to add aerodynamic effects to specific airplane components and aerodynamic coefficients. The total aerodynamic coefficients are the aggregate of the coefficient contributions of individual airplane components due to the relevant aerodynamic effects. In general, the aerodynamic coefficients are functions of a large number of variables, including the angle of attack, side slip angle, speed, deflection of flaps and control surfaces, deployment of landing gear, and proximity to the ground. To cover an entire arbitrary flight, the computational fluid dynamics (CFD) data is combined with mathematical, semi-empirical, and empirical methods for modeling additional aerodynamic effects which were not considered in the CFD simulations. In the design phase of the airplane, this approach is particularly advantageous as it reduces the computational cost related to CFD and allows for rapid evaluations of design updates.
Keywords: aerodynamic databank, aerodynamic modeling, flight dynamics, aircraft development, component buildup method, stability derivatives, aerodynamic coeffi cients, in-flight icing, electric airplane